Defects and improving the maintainability of buildings at the advance technical training centres - Rajandran Suppiah Raman, 1958-; Mohd. Nadzri Jaafar; Fakulti Geoinformasi dan Harta Tanah (2011)
Thesis (Sarjana Sains (Pengurusan Aset dan Fasiliti)) - Universiti Teknologi Malaysia, 2011